2008
DOI: 10.1515/epoly.2008.8.1.935
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of dope concentration and jetdrawing on structure development of wet-spun poly(acrylonitrile)

Abstract: Acrylic fibers are the major precursor of carbon fibers. In this work, the synergistic effect of polymer concentration and jet stretching on porosity, morphology and mechanical properties of wet-spun poly(acrylonitrile) fibers were studied and then the role of void size was elucidated. The results showed that the effect of jet stretching on fiber porosity is negligible below a threshold polymer concentration. Increasing polymer concentration up to 20 vol. % reduced the total porosity significantly but increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In comparison with freely spun fibers, the pores in cross-section of jet stretched PAN and PAN/CNT fibers were smaller and narrower. The residence time of filaments in the coagulation bath was shortened by jet stretch, reducing the available time for nucleation and growth of voids, resulting in fibers with lower porosity [37,38]. Arbab et al [37,39] has also observed more compact structure with smaller voids by increasing the jet stretch ratio in wet spinning of PAN fibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with freely spun fibers, the pores in cross-section of jet stretched PAN and PAN/CNT fibers were smaller and narrower. The residence time of filaments in the coagulation bath was shortened by jet stretch, reducing the available time for nucleation and growth of voids, resulting in fibers with lower porosity [37,38]. Arbab et al [37,39] has also observed more compact structure with smaller voids by increasing the jet stretch ratio in wet spinning of PAN fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The residence time of filaments in the coagulation bath was shortened by jet stretch, reducing the available time for nucleation and growth of voids, resulting in fibers with lower porosity [37,38]. Arbab et al [37,39] has also observed more compact structure with smaller voids by increasing the jet stretch ratio in wet spinning of PAN fibers. In addition, the applied tension on fibers during jet stretch makes the fiber thread thinner, limits the mobility of polymer parts, and hinders the counter-diffusion of solvent/nonsolvent.…”
Section: Resultsmentioning
confidence: 99%
“…In both methods polymer is dissolved into solution and the polymer solution is filtrated, dearated, and pumped through the spinneret [43]. In dry spinning, solvents are removed by thermal evaporation while in wet spinning the coagulation of the polymer is carried out in another fluid that is compatible with the spinning solvent but is not itself a solvent for the polymer [44,45] In practice, as the viscose polymer solution enters into the coagulation bath, phase separation begins due to solvent out-flow and nonsolvent inflow and the polymer precipitates as fibrils [46,47]. There is several studies used solution spinning to produce PLGA fibers [48][49][50][51][52][53][54][55][56].…”
Section: Wet Spinningmentioning
confidence: 99%
“…These variables can be separated in three categories namely polymer solution parameters, processing conditions and ambient parameters like temperature and humidity. In recent years, effect of wet‐spinning parameters on different properties of fibers has been studied through experimental observations . For example, Puppi et al .…”
Section: Introductionmentioning
confidence: 99%